Antioxidant Effect of Dill (Anethum graveolens Boiss.) Oil in Crude Soybean Oil and Comparison with Chemical Antioxidants - F Ayoughi; M Barzegar; MA Sahari; H Naghdi Badi (Institue of Medicinal Plants, ACECR, 2009)
Background: Today, the growing interest has been focused on the use of medicinal plants and their active components as natural sources, due to their well-known abilities to scavenge free radical. Antioxidant effectively and to different ways can prevent from reaction free radical with biomolecules (e.g., protein, amino acids, lipid and DNA) and cause reducing cell injury and death, chronic diseases and cancers. Objective: To determine the chemical composition and antioxidant properties of the essential oil of Anethum graveolens Boiss. in crude soybean oil. Methods: In this study, essential oil was obtained from the seeds and it was analyzed by GC/MS. The chemical compositions were identified. The antioxidant activity was investigated with two methods, DPPH free radical scavenging and β-carotene/linoleic acid. Also, antioxidant activity of essential oil was determined by measuring peroxide and thiobarbituric acid values in crude soy bean oil and results were compared with synthetic antioxidant BHT and BHA. Results: Results showed that six major components in the essential oil were: D-carvone (36.09%), limonene (19.89%), dill apiole (16.83%), E-dihydrocarvone (7.36%), Z-dihydrocarvone (6.59%) and thymol (6.5%). In DPPH∙ system, the EC50 value of Anethum graveolens essential oil was determined as 2.57 ± 1.52 mg/ml. This parameter for BHT was 0.016 ± 0.001. By the β-carotene bleaching system, antioxidant activity of essential oil at 7 mg/ml (77.29%) that was almost equal to BHT at 0.1 mg/ml. In oven test, essential oil could inhibit of primary and secondary oxidation products of crude soy bean oil at 0.6 mg/ml that was almost equal to BHA at 0.1 mg/ml. Conclusion: Results showed that the essential oil of Anethum graveolens could be used as a natural antioxidant in foodstuffs after complementary tests and it causes functionality in them.